Management of innovative projects to ensure innovative development of enterprises - Olena Iastremska; Lyudmyla Malyarets; Viktoriia Samoilenko; Oleksii Budarin (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study is theoretical provisions, methodology of adaptive management of innovation projects and innovative development of enterprises, methodological basis, practical proposals for its research in modern conditions. The purpose of the article is to summarize generalization of the theoretical basis of the features of innovative projects, the expediency of using organizational structures for managing the processes of their formation and implementation, analysis of adaptive methodologies for managing innovative projects to ensure the employment of workers, their innovative development, and development of practical recommendations on these issues for a working enterprise. The purpose is revealed by solving the following tasks: generalize the features of innovative projects that determine the success of their implementation; determine the feasibility of using organizational structures of enterprise management for the formation and implementation of innovative projects to ensure innovative development; identify and propose the use of adaptive management methodologies for innovative projects to achieve successful innovative development of enterprises; develop a hybrid organizational structure for innovation management; the main directions of innovative personnel management of enterprises to promote their employment and management of innovative development are proposed. To solve the tasks, the following methods were used: theoretical generalization, analysis, synthesis, induction and deduction, structural and logical analysis, systemic and situational approaches, the method of working day photography, Agile adaptive management methodology, graphic method, and the authors' own practical experience. The conclusions and results of the article are as follows: it is proved that the management of innovation projects should take into account their features, be based on the use of project, matrix and hybrid organizational management structures and the application of adaptive methodologies for managing innovation development and the formation and implementation of innovation projects, such as Agile, Scrum, Kanban, Lean. For the operating enterprise Nebozvid LLC, using adaptive management methodologies, a hybrid organizational structure of the project department has been developed to ensure the innovative development of the enterprise through the implementation of innovative projects with the organization of small project teams. The main trends in innovative personnel management of enterprises are proposed, the use of which contributes to the success of innovative project management to ensure the innovative development of enterprises.